A Standardized Approach to Recommending Diagnostic Criteria in Chinese Clinical Practice Guidelines - ZHOU Qi; LI Qinyuan; HE Hongfeng; PENG Dongrui; ZHANG Huayu; WANG Ye; YANG Kehu; CHEN Yaolong (Xiehe Yixue Zazhi)
Diagnostic criteria, as a critical component of clinical practice guidelines, play a direct role in guiding clinicians' diagnostic and treatment decisions. Although China has increasingly emphasized the development and updating of clinical guidelines in recent years, research focusing on the diagnostic criteria within these guidelines remains limited. This paper aims to explore the types of diagnostic criteria, the issues they present, and the processes involved in their formulation. Based on this analysis, suggestions are proposed to improve the recommendation and application of diagnostic criteria in Chinese guidelines.